Sistem Pembuangan Sampah Pada Ruang Terbuka Hijau Ditepian Sungai Kayan Tanjung Selor - Eko Wahyudi (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
Tanjung Selor is one of the sub-districts located on the banks of the Kayan River, Bulungan Regency, North Kalimantan Province. Where green open space (RTH) on the riverbank is one of the buffers of environmental quality. Lack of concern for the environment which causes damage to nature, small examples such as throwing garbage into the river or in the green space. To obtain an overall picture and collect valid data about this research, the research method approach used is by direct field observation and field data mining related to existing conditions in the field, such as trash cans on the banks of rivers causing visitors to litter. The purpose of this study is to find out how big the application of the garbage disposal system is in the RTH on the banks of the Kayan River, Tanjung Selor.